The Cultural Role of Traditional Leaders in Initiating The Formulation of Sharia Regional Regulations in West Sumatra - Mughits, Abdul; Syafruddin; Fathorrahman (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Abstract This research aims to explore and analyze the role of the traditional leaders (Ninik Mamak) in West Sumatra in initiating and controlling the implementation of Sharia Regional Regulations (Perda Syariah) and how they act as a bridge between culture and religion. These traditional leaders play an important role in maintaining the balance between Minangkabau customs and the principles of Islamic law. The data sources for this qualitative research were the results of observations of Minangkabau customary life phenomena, interviews with Minangkabau customary figures and relevant parties, and documentation of research findings and news related to the Sharia Regional Regulation in West Sumatra. After analyzing the data using a sociological approach, specifically Max Weber's theories of Charisma and Authority, it was found that the traditional leaders of the Ninik Mamak played a significant role in initiating and controlling the implementation of the Sharia Regional Regulation in West Sumatra, while also taking on a moderating role between culture and religion. This is in line with the motto